Follow-up investigation of open trigger digit release - Cakmak, Fedaye; Wolf, Maya Barbara; Bruckner, Thomas; Unglaub, Frank (Archives of orthopaedic and trauma surgery, 2012)
PurposeThe purpose of this retrospective study was to identify the postoperative complications and disorders associated with open trigger finger release. Factors that were investigated by this study included demographic details, the number of digits affected, BMI, level of manual strain, trauma, received systemic medication, hand dominance, pre-treatment with steroid injection, and concomitant diseases.MethodsOne hundred and three patients, who underwent open release surgery for 117 trigger fingers and thumbs, were followed up until complete resolution of all complaints. Patients’ age, BMI, hand dominance, occupational manual strain, and previous medical history regarding trigger finger or thumb were obtained. Associated conditions and medical treatment, trauma, and previous hand surgical interventions were included as well. Details regarding duration of complaints, ROM, visual analogue pain scale, swelling, recurrence of the disease following previous surgical release, and persistence of complaints following corticosteroid injection were examined.ResultsThe dominant hand was not significantly more frequently affected than the non-dominant hand. Occupation also did not influence the incidence of trigger digit. Patients with systemic steroid therapy had a significantly shorter duration of postoperative symptoms with a mean duration of 29.3 days (range, 28-31 days ± 1.3). Significantly less postoperative swelling was noticed in patients with a pre-surgical steroid injection. The mean duration of symptoms before and after surgery was significantly shorter for a trigger thumb than for trigger finger.DiscussionOpen trigger digit release constitutes an adequate low-risk surgical procedure for treatment of trigger digit. In this study, we could show that the incidence of this disease is not significantly correlated with the manual strain, trauma, BMI, hand dominance or concomitant diseases like diabetes mellitus, rheumatoid arthritis, renal insufficiency, and hypothyroidism. Additionally, this study illustrates the importance of a careful postoperative follow-up treatment to avoid potential persistent functional limitations.
Gesehen am 06.04.2018